The U.S. consumption-wealth ratio and foreign stock markets: International evidence for return predictability - Thomas Nitschka (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
A simple manipulation of the cointegrated framework proposed by Lettau and Ludvigson (2001, 2004) allows to demonstrate that temporary fluctuations of the U.S. consumption-wealth ratio predict excess returns on international stock markets. This finding is the reflection of an important common, temporary component in international stock markets and thus provides empirical evidence for a robust link between stock markets at business cycle frequency. Moreover, I find that between one third and more than a half of the covariation of long-horizon returns on the G7 stock markets is explained by the common transitory stock market component identified in this paper. Furthermore, U.S. households seem to rebalance their foreign equity portfolio in response to the perception of local currency rather than exchange rate adjusted returns.
Keywords: G12; E21; 519; Cointegration; Consumption-wealth ratio; Stock return predictability